Correction: A disordered encounter complex is central to the yeast Abp1p SH3 domain binding pathway. - Gabriella J Gerlach; Rachel Carrock; Robyn Stix; Elliott J Stollar; K Aurelia Ball (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1007815.].